2018
DOI: 10.1093/nar/gky796
|View full text |Cite
|
Sign up to set email alerts
|

3′ end additions by T7 RNA polymerase are RNA self-templated, distributive and diverse in character—RNA-Seq analyses

Abstract: Synthetic RNA is widely used in basic science, nanotechnology and therapeutics research. The vast majority of this RNA is synthesized in vitro by T7 RNA polymerase or one of its close family members. However, the desired RNA is generally contaminated with products longer and shorter than the DNA-encoded product. To better understand these undesired byproducts and the processes that generate them, we analyze in vitro transcription reactions using RNA-Seq as a tool. The results unambiguously confirm that product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
149
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(163 citation statements)
references
References 35 publications
14
149
0
Order By: Relevance
“…Altogether, the intact mass and denaturing gel analyses of the short IVT templates suggest that during IVT spurious, 3'-extended products are synthesized in the reaction and some of these can form dsRNA structures, supported by their RNase III sensitivity. These observations are consistent with a recent study that demonstrated the synthesis of a heterogeneous population of 3'extended RNA products during IVT from a completely unrelated DNA template [20].…”
Section: '-Extended Byproducts Are Formed During Ivtsupporting
confidence: 93%
See 4 more Smart Citations
“…Altogether, the intact mass and denaturing gel analyses of the short IVT templates suggest that during IVT spurious, 3'-extended products are synthesized in the reaction and some of these can form dsRNA structures, supported by their RNase III sensitivity. These observations are consistent with a recent study that demonstrated the synthesis of a heterogeneous population of 3'extended RNA products during IVT from a completely unrelated DNA template [20].…”
Section: '-Extended Byproducts Are Formed During Ivtsupporting
confidence: 93%
“…In contrast, reactions performed at 50°C did not show any detectable 3'-extended products ( Figure 3D). In conclusion we find that consistent with previous studies, T7 RNA polymerase can efficiently 3'-extend run-off transcripts [20], and that high-temperature IVT reduces the 3'extension of the run-off product.…”
Section: High-temperature Ivt Prevents the Self-priming Of The Run-ofsupporting
confidence: 92%
See 3 more Smart Citations